Towards responsive regulation of the Internet of Things: Australian perspectives - Megan Richardson; Rachelle Bosua; Karin Clark; Jeb Webb; Atif Ahmad; Sean Maynard (Internet Policy Review, 2017)
The Internet of Things (IoT) is considered to be one of the most significant disruptive technologies of modern times, and promises to impact our lives in many positive ways. At the same time, its interactivity and interconnectivity poses significant challenges to privacy and data protection. Following an exploratory interpretive qualitative case study approach, we interviewed 14 active IoT users plus ten IoT designers/developers in Melbourne, Australia to explore their experiences and concerns about privacy and data protection in a more networked world enabled by the IoT. We conclude with some recommendations for 'responsive regulation' of the IoT in the Australian context.
Keywords: 300; Internet of things; Innovation